Depressor Septi Nasi Modifications in Rhinoplasty: A Review of Anatomy and Surgical Techniques - Benlier, Erol; Balta, Serkan; Tas, Suleyman (Facial Plastic Surgery, 2014)
The anatomy of the nasal muscles contributes a social harmony in aesthetic rhinoplasty because these muscles coordinate the nose and the upper lip while smiling. Sometimes this coordination can be interrupted by the hyperactivity or variations of these muscles and may result as a deformity because of their dynamic functions and relations with the nose. In our daily practice, we usually perform the rhinoplasty without considering the dynamic functions. When the patients recover the muscle functions after operation and start to use their mimics, such as smiling, the undamaged dynamic forces may start to rotate the tip of the nose inferiorly in a long-term period, correlated with their preoperative function. To avoid this unexpected rotation it is essential to remember preoperative examination of the smile patterns. To manage this functional part of rhinoplasty, we aimed to clarify the smiling patterns or deformities mainly focused on depressor septi nasi muscle in this article. This muscle creates downward movement of the nasal tip and shortens the upper lip during smiling. The overactivity of this muscle can aggravate the smiling deformity in some patients by a sharper nasolabial angle correlated with levator labii superioris alaeque nasi and orbicularis oris muscle activities. The article not only stresses the correction of this deformity, but also aims to guide their treatment alternatives for correlation of postoperative results and applicability in rhinoplasty.
Keywords: smiling deformity; depressor septi nasi muscle; nasal tip; rhinoplasty